Multiomics Analyses Identify Genes and Pathways Relevant to Essential Tremor. Issue 7 (6th April 2020) - Liao, Calwing; Sarayloo, Faezeh; Rochefort, Daniel; Houle, Gabrielle; Akçimen, Fulya; He, Qin; Laporte, Alexandre D.; Spiegelman, Dan; Poewe, Werner; Berg, Daniela; Müller, Stefanie; Hopfner, Franziska; et al.
Abstract: Introduction: The genetic factors and molecular mechanisms predisposing to essential tremor (ET) remains largely unknown. Objective: The objective of this study was to identify pathways and genes relevant to ET by integrating multiomics approaches. Methods: Case‐control RNA sequencing of 2 cerebellar regions was done for 64 samples. A phenome‐wide association study (pheWAS) of the differentially expressed genes was conducted, and a genome‐wide gene association study (GWGAS) was done to identify pathways overlapping with the transcriptomic data. Finally, a transcriptome‐wide association study (TWAS) was done to identify novel risk genes for ET. Results: We identified several novel dysregulated genes, including CACNA1A and SHF . Pathways including axon guidance, olfactory loss, and calcium channel activity were significantly enriched. The ET GWGAS data found calcium ion‐regulated exocytosis of neurotransmitters to be significantly enriched. The TWAS also found calcium and olfactory pathways enriched. The pheWAS identified that the underexpressed differentially expressed gene, SHF, is associated with a blood pressure medication ( P = 9.3E‐08), which is used to reduce tremor in ET patients. Treatment of cerebellar DAOY cells with the ET drug propranolol identified increases in SHF when treated, suggesting it may rescue the underexpression. Conclusion: We found that calcium‐related pathways were enriched across the GWGAS, TWAS, and transcriptome. SHF was shown to have significantly decreased expression, and the pheWAS showed it was associated with blood pressure medication. The treatment of cells with propranolol showed that the drug restored levels of SHF . Overall, our findings highlight the power of integrating multiple different approaches to prioritize ET pathways and genes. © 2020 International Parkinson and Movement Disorder Society